Increased antiretroviral therapy prescription and HIV viral suppression among persons receiving clinical care for HIV infection. (24th August 2016) - Bradley, Heather; Mattson, Christine L.; Beer, Linda; Huang, Ping; Shouse, R. Luke
Abstract : Objective: To assess trends during 2009–2013 in antiretroviral therapy (ART) prescription and viral suppression among adults receiving HIV clinical care in the United States. Design: We used data from the Medical Monitoring Project, a surveillance system producing national estimates of characteristics of HIV-infected adults receiving clinical care in the United States. Methods: We estimated weighted proportions of persons receiving HIV medical care who were prescribed ART and achieved HIV viral suppression (<200 copies/ml) at both last test and at all tests in the previous 12 months during 2009–2013. We assessed trends overall and by gender, age, race/ethnicity, and sexual behavior/orientation. Results: ART prescription and viral suppression increased significantly during 2009–2013, overall and in subgroups. ART prescription increased from 89 to 94% ( P for trend <0.01). Viral suppression at last measurement increased from 72 to 80% ( P for trend <0.01). The largest increases were among 18–29 year olds (56–68%), 30–39 year olds (62–75%), and non-Hispanic blacks (64–76%). Sustained viral suppression increased from 58 to 68% ( P for trend <0.01). The largest increases were among 18–29 year olds (32–51%), 30–39 year olds (47–63%), and non-Hispanic blacks (49–61%). Conclusion: Adults receiving HIV medical care are increasingly likely to be prescribed ART and achieve viral suppression. Recent efforts to promote early antiretroviral therapy use may have contributed to these increases, bringing us closer to realizing key goals of the National HIV/AIDS Strategy.